Atmospheric Corrosion Study of Metals in an Industrial Environment - Vashi, R.T.; Kadiya, H.K. (Asian Journal of Chemistry, 2010)
Corrosion rate of mild-steel (MS), zinc and aluminum as well as the sulphation rate was determined during 2005-2006 under outdoor exposure in an industrial environment at Vapi (Dist. Valsad) situated in South Gujarat, India. Monthly corrosion rate vary from 650 to 2014, 54 to 160 and 1.9 to 27.5 mg/dm2 correspond to mild-steel, zinc and aluminium respectively, whereas the yearly corrosion rate vary from 9109 to 23495, 211 to 890 and 18.9 to 58.0 mg/dm2 for mild-steel, zinc and aluminium respectively. Monthly corrosion rate was found in the decreasing order : mild steel > zinc > aluminium. Corrosion rate of these three metals was found more in rainy seasons than the rate of winter and summer season. There is a considerable loss of corrosion rate during exposure for one year of mild steel. Monthly corrosion rate of mild steel indicate a close correlationship with rainfall (r = 0.81), number of rainy days (r = 0.98) and satisfactory correlation with sulphation rate (r = 0.43). No correlation appeared to exist between temperature and corrosion rate of mild-steel, zinc and aluminium. The X-ray diffraction analysis of mild-steel corrosion product was also performed.